2015
DOI: 10.1055/s-0034-1391852
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and implications of a 48-h cutoff for video capsule endoscopy application in overt obscure gastrointestinal bleeding

Abstract: Background and study aims: Early video capsule endoscopy (VCE) may provide a high diagnostic yield and improve clinical outcomes in patients with overt obscure gastrointestinal bleeding (OGIB); however, there is no practical recommendation for the ideal timing of VCE application in overt OGIB. Therefore, this study investigated the diagnostic yield and efficacy of VCE to assess overt OGIB with respect to the timing of application. Patients and methods: We retrospectively enrolled patients who had undergone VCE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 22 publications
4
17
0
1
Order By: Relevance
“…[ 34 ] This is important, especially for the detection of bleeding, where time might be critical. [ 35 ] Technical staff is already being trained for the viewing of the capsule video. [ 36 38 ] Our data show that precise indication for CE by a gastroenterologist leads to better diagnostic yield, and as a consequence makes treatment decisions possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 34 ] This is important, especially for the detection of bleeding, where time might be critical. [ 35 ] Technical staff is already being trained for the viewing of the capsule video. [ 36 38 ] Our data show that precise indication for CE by a gastroenterologist leads to better diagnostic yield, and as a consequence makes treatment decisions possible.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to radiographic imaging techniques, CE is highly sensitive in the detection of occult arterial and venous bleeding, especially if done during bleeding episodes. [ 35 ] Its sensitivity is higher than CT-angiography or magnetic resonance enteroclysis. [ 39 ] Nevertheless, blood flow rates for bleeding detection by CE have not yet been described.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing different groups according to the timing of CE, previous studies have shown that the earlier the capsule study is started, the greater the DY achieved[ 13 , 16 , 25 - 30 ]. Several studies evaluating the timing from overt-OGIB to CE, such as 48-72 h[ 16 , 25 , 27 ], 1 wk[ 28 ], 10 d[ 29 ], 15 d[ 30 ] have already been reported, demonstrating that the DY was always superior whenever CE was performed earlier. In our study, that association was not found, since independently from the timing of CE, the DY was similar between all periods examined ( P > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Using CE early in the course of overt-OGIB seems to be attractive, because of the higher DY, and even if no lesion is found, at least, it has the potential to localize the source of the bleeding[ 12 - 15 ]. However, the data is limited and the optimal timing for CE in overt-OGIB remains unclear[ 1 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is highly acceptable that the sooner CE is performed, the higher the diagnostic value. CE within 2 days of the last overt gastrointestinal bleeding after negative bidirectional endoscopic findings could improve the management of these patients providing a more rapid, appropriate and cost-effective therapeutic plan [ 25 ]. CE was better than CTA in a previous study [ 26 ].…”
Section: Discussionmentioning
confidence: 99%